Interaction between potyvirus and crinivirus in sweet potato - Flamarique, Sofia Solange (2020)
Sweet potato, in Argentina, is affected by the “encrespamiento amarillo”, a viral disease in which seven viruses are involved, among them two potyvirus (sweet potato feathery mottle virus - SPFMV and sweet potato virus G - SPVG) and a crinivirus (sweet potato chlorotic stunt virus - SPCSV). This research aimed to study the interaction between SPFMV and SPVG with SPCSV in sweet potato. Two sweet potato cultivars (Gem and Arapey INIA) and Ipomoea setosa as an indicator susceptible plant were tested as single (SPFMV or SPVG), double (SPFMV + SPVG, SPFMV + SPCSV or SPVG + SPCSV) or triple (SPFMV + SPVG + SPCSV) grafts. Both potyviruses were purified and the viral concentrations in the plant tissues were quantified by the DAS-Elisa method. The viruses and their severities were evaluated at 7, 15, 21, 30 and 35 days post-inoculation. A synergistic effect was observed with the three viruses in the indicator plant. The viral concentration increase was 50 times for SPFMV (day 35) and two times for SPVG (day 21) in the Gem cultivar, and 1.89 times for SPFMV (day 35) and three times for SPVG (day 7) in the Arapey INIA. For multiple infections, the indicator plant and the Gem cultivar exhibited synergistic symptoms and increase in the viral titers, with a higher severity and variability of the symptoms. Co-infections such as SPFMV + SPVG showed characteristic potyvirus symptoms, without increasing the viral concentrations; triple co-infections exhibited viral complex symptoms, with increase in the potyvirus titers; and the symptoms were mild or imperceptible in the simple infections.